IMRT and HDR-ICBT for Locally Advanced Clear Cell Adenocarcinoma of the Cervix in Uterus Didelphys Associated With Unilateral Renal Agenesis - Lei, Chengzhi; Huang, Manni; Li, Ning; An, Jusheng; Xiong, Suiyang; Li, Xiaoguang; Wu, Lingying (Frontiers in Oncology, 2020)
Clear cell adenocarcinoma of the cervix (CCAC) with genitourinary malformations is rare. Here we report a case of CCAC in uterus didelphys (UD) associated with unilateral renal agenesis (URA) that was treated with intensity-modulated radiotherapy (IMRT) and high-dose rate intracavitary brachytherapy(HDR-ICBT). We also retrospectively reviewed the medical records of CCAC cases with genitourinary malformations treated at National Cancer Center/Cancer Hospital (Beijing, China) between December 2006 and June 2017. Eight cases of this rare condition were identified by pathologic diagnosis. Seven patients received surgical treatment including radical hysterectomy (n=4), modified radical hysterectomy (n=1), and total hysterectomy (n=2). Five patients received adjuvant radiotherapy and chemotherapy after surgery. One patient with CCAC in UD associated with URA was treated with radical IMRT and adjuvant chemotherapy. The 8 patients were followed up for an average of 7.9 years; in 7 cases, there was no evidence of disease recurrence, while 1 patient relapsed and died after 1.5 years of treatment. Based on these findings, locally advanced CCAC in UD associated with URA can be effectively treated with radical IMRT.